Kebersamaan di Ruang Publik pada Pawai Perayaan Gotong Toa Pe Kong Berbasis Masyarakat Majemuk di Slawi Pasca Orde Baru 2010 - Zeffry Alkatiri; Fabianus H Koesoemadinata (Antropologi Indonesia, 2012)
This article observes collective action of Toa Pe Kong celebration in the public space during Post-New Order era in Slawi, Central Java. This celebration involves local people from different religions and cultures. Why this celebration can be done after New Order? What aspect functions as collective bond among Slawi plural society? Using historical and cultural sources, this study analyses function and meaning of the ritual in relation to the collective aspect of Toa Pe Kong celebration. Keywords: collective, public space, Toa Pe Kong, Slawi